Design and real-time implementation of a PMU-based adaptive auto-reclosing scheme for distribution networks. (February 2019) - Monadi, Mehdi; Hooshyar, Hossein; Vanfretti, Luigi
Highlights: The paper presents a PMU-based autoreclosing method. The paper presents a comprehensive auto-reclosing method for all fault types. The proposed method can enhance the reliability of distribution systems. Effects of thermal stress and stability indices are investigated before reclosing. The proposed method has been evaluated using real-time HIL simulation method. Abstract: This paper presents an adaptive auto reclosing scheme (AARS), applicable to active distribution systems, which are equipped with Phasor Measurement Units (PMUs). The scheme differentiates between temporary and permanent faults by taking into account the operational conditions of the network when determining the reclosing dead time. The performance of the proposed scheme is assessed through a real-time hardware-in-the-loop (HIL) simulation test setup.